Russian Emigrant Community in Toulon in 1920-1930-s: Formation and Composition - M. M. Rudkovskaya (Научный диалог)
The process of formation of the Russian emigrant colony in the South French city of Toulon in the period between world wars is considered. The relevance and novelty of this study is determined by the fact that it is based on an extensive set of archival documents, first introduced into scientific circulation, the history of the formation of a new center of Russian emigration in France is examined. Analyzing the process of formation of the Russian community in this region, the author pays attention to the political events that preceded the appearance of Russian immigrants in the city. The article describes the economic and socio-cultural context of the city at the time of arrival of refugees. The paper presents the results of a comparative analysis of statistical data on the quantitative and gender composition of the Russian community of Toulon in the studied period. The question of social and professional belonging of this group of immigrants is raised. It is shown that the process of formation and change in the composition of the Russian colony in Toulon is inscribed in the overall economic context of the region. It is emphasized that one of the important factors that influenced the development of the Russian community was the lack of stable links between the labour integration of immigrants and the choice of place of residence. The author dwells on the problem of intra-community relations and external factors that influenced the changes in the quantitative composition of the Russian community.